Quiescent NIR and optical counterparts to candidate black hole X-ray binaries. Issue 2 (16th October 2018) - López, K M; Jonker, P G; Torres, M A P; Heida, M; Rau, A; Steeghs, D
ABSTRACT: We present near-infrared and optical imaging of 15 candidate black hole X-ray binaries. In addition to quiescent observations for all sources, we also observed two of these sources (IGR J17451−3022 and XTE J1818−245) in outburst. We detect the quiescent counterpart for 12 out of 15 sources, and for the remaining 3, we report limiting magnitudes. The magnitudes of the detected counterparts range between K s = 17.59 and K s = 22.29 mag. We provide (limits on) the absolute magnitudes and finding charts of all sources. Of these 12 detections in quiescence, 7 detections represent the first quiescent reported values (for MAXI J1543−564, XTE J1726−476, IGR J17451−3022, XTE J1818−245, MAXI J1828−249, MAXI J1836−194, Swift J1910.2−0546), and 2 detections show fainter counterparts to XTE J1752−223 and XTE J2012+381 than previously reported. We used theoretical arguments and observed trends, for instance between the outburst and quiescent X-ray luminosity and orbital period P orb to derive an expected trend between Δ K s and P orb of$Δ K_{\rm s} \propto \log P_{\rm orb}^{0.565}$ . Comparing this to observations, we find a different behaviour. We discuss possible explanations for this result.